Efficacy and safety of praziquantel in preschool-aged children in an area co-endemic for Schistosoma mansoni and S. haematobium. - Jean T Coulibaly; Yve K N'gbesso; Stefanie Knopp; Jennifer Keiser; Eliézer K N'Goran; Jürg Utzinger (Public Library of Science (PLoS), 2012)
In sub-Saharan Africa the recommended strategy to control schistosomiasis is preventive chemotherapy. Emphasis is placed on school-aged children, but in high endemicity areas, preschool-aged children are also at risk, and hence might need treatment with praziquantel. Since a pediatric formulation (e.g., syrup) is not available outside of Egypt, crushed praziquantel tablets are used, but the efficacy and safety of this treatment regimen is insufficiently studied.We assessed the efficacy and safety of crushed praziquantel tablets among preschool-aged children (<6 years) in the Azaguié district, south Côte d'Ivoire, where Schistosoma mansoni and S. haematobium coexist. Using a cross-sectional design, children provided two stool and two urine samples before and 3 weeks after treatment. Crushed praziquantel tablets, mixed with water, were administered at a dose of 40 mg/kg. Adverse events were assessed and graded 4 and 24 hours posttreatment by interviewing mothers/guardians.Overall, 160 preschool-aged children had at least one stool and one urine sample examined with duplicate Kato-Katz thick smears and a point-of-care circulating cathodic antigen (POC-CCA) cassette for S. mansoni, and urine filtration for S. haematobium diagnosis before and 3 weeks after praziquantel administration. According to the Kato-Katz and urine filtration results, we found high efficacy against S. mansoni (cure rate (CR), 88.6%; egg reduction rate (ERR), 96.7%) and S. haematobium (CR, 88.9%; ERR, 98.0%). POC-CCA revealed considerably lower efficacy against S. mansoni (CR, 53.8%). Treatment was generally well tolerated, but moderately severe adverse events (i.e., body and face inflammation), were observed in four Schistosoma egg-negative children.Crushed praziquantel administered to preschool-aged children at a dose of 40 mg/kg is efficacious against S. mansoni and S. haematobium in a co-endemic setting of Côte d'Ivoire. Further research is required with highly sensitive diagnostic tools and safety must be investigated in more depth.Controlled-Trials.com ISRCTN53172722.